ALTERNATIVE ASSESSMENTS IN READING : MAKING THE TEST MORE AUTHENTIC - Wiyaka Wiyaka (Universitas PGRI Semarang, 2012)
This paper tries to evaluate the exisence of reading test format used in national exam which has been applied for many many years in our schools.As we know that under the reasons of practicality and and limited budget from the government, a multiple choice type is used to assess the students’ language competence. Logically, language competence is not only assessed through recognition test, but also production test.In that way then it is regarded important to provide test types other than traditional test in the hope that the test does not only function as a way to measure the product of learning, but also the proses of learning.Some alternative assessments will be discussed and offered to the language practitioners.